We testify with our lives : how religion transformed radical thought from black power to Black Lives Matter - Johnson, Terrence L. (Columbia series on religion and politics., 2021)
"Police killings of unarmed Black people have ignited a national and international response unlike any in decades. But differing from their civil rights-oriented predecessors, today's activists do not think that the institutions and values of liberal democracy can eradicate structural racism. They draw instead on a Black radical tradition that, Terrence L. Johnson argues, derives its force from its unacknowledged ethical and religious dimensions. We Testify with Our Lives traces Black religion's sustained influence from SNCC to the present, reconstructing a radical lived ethics of freedom and justice. Johnson demonstrates that Black Power fundamentally contests liberalism's abstract understanding of democracy, calling instead for new embodied frameworks to achieve human flourishing and dignity. Black bodies represent the primary form of resistance against violent and oppressive regimes of white supremacy and exploitation, and the individual and collective struggles of Black life bear witness to the dogged determination to cultivate beauty, rage, and joy. Considering the writings of Audre Lorde, Toni Cade Bambara, Stokely Carmichael, Martin Luther King Jr., Malcolm X, and James Baldwin, We Testify with Our Lives makes its case through a new narrative of the evolution of Black radicalism from the civil rights movement through the Movement for Black Lives. It forges new insights into Black Power's vital contributions to debates on ethics, transnational politics, democracy, political solidarity, and freedom-and its potent resources for the ongoing struggle to build democratic possibilities for all"--